Teachers’ and Parents’ Effort in Character Building of Students with Austism in Public Special School A Cimahi - Lili Halimah; Ernandia Pandikar; Nurul Azhari (Program Studi bimbingan Konseling PPs UNM Makassar, 2021)
This study attempts to encourage character building of students with special needs, especially the character of independence. Being independent serves as one of primary education goals for children with autism to reduce dependence towards others and to raise sense of responsibility in their daily lives. Qualitative method is applied in this study in which the researcher investigates natural objects and plays a role as the key instrument. Data collection technique was done through triangulation, data analysis was performed inductively, and research findings highlighted more on the meaning instead of generalizatibility. The data collection technique is tentative in nature. During the research process, research questions were solved through collecting and analyzing information gathered from related participants. The interview technique is generally distinguished into 2 namely 1) structured interview and 2) unstructured interview. The finding of this research reveals that the character of being independent in children with special needs can be promoted by habituation to involve children in daily activities as well as during online learning.